Translanguaging Pedagogies and the Making of Literate Multilinguals: A Cognitive and Sociocultural Inquiry - Robert lLston Omari Otieno (Universitas Galuh, 2026)
Translanguaging has emerged as a powerful pedagogical strategy in multilingual classrooms, offering students the opportunity to leverage all their linguistic resources for learning. This paper investigates how translanguaging practices shape learners’ metalinguistic awareness and literacy development across both dominant and marginalized languages. Drawing on sociocultural and cognitive-linguistic frameworks, the study examines classroom interactions, literacy assessments, and student reflections in multilingual African contexts. Findings are expected to reveal that translanguaging enhances students’ ability to reflect on language structures, fosters literacy skills across multiple languages, and strengthens learners’ linguistic and cultural identities. By situating these insights within broader debates on multilingual education and language equity, the research highlights how inclusive pedagogical approaches can address literacy disparities and promote cognitive and socio-emotional growth. The study contributes to ongoing discussions in applied linguistics, education, and sociolinguistics by providing empirical evidence on the efficacy and transformative potential of translanguaging in contemporary classrooms.